2009
DOI: 10.1002/ajh.21571
|View full text |Cite
|
Sign up to set email alerts
|

Tumor flare reactions and response to lenalidomide in patients with refractory classic Hodgkin lymphoma

Abstract: Sickle-cell disease is not a reportable condition, making it difficult to ascertain the number of affected individuals. We estimated the number of people with sickle-cell disease for the United States and each individual state, adjusting for increased mortality. US Census population data for each of the 50 states plus the District of Columbia were obtained. The published prevalence of sickle-cell disease for blacks and Hispanics of either Mexican or non-Mexican ancestry was applied. Analysis revealed 89,079 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In particular, strategies aimed at interfering with the crosstalk between RS cells and their cellular accomplices should take into account that the same cellular subset may play different, even opposite, functions according to the signals it senses. This suggests a note of caution regarding the adoption of therapies able to alter the composition of the HL-associated microenvironment, such as monoclonal-antibody-based humoral immunotherapies (e.g., Rituximab) or immunomodulatory drugs (e.g., lenalidomide) [138, 139]. On the other hand, other target therapies such as anti-CD30 antibodies and anti-NFkB drugs may provide a significant benefit in the limited but still significant fraction of chemoresistant HL patients.…”
Section: Extranodal Involvement By Hlmentioning
confidence: 99%
“…In particular, strategies aimed at interfering with the crosstalk between RS cells and their cellular accomplices should take into account that the same cellular subset may play different, even opposite, functions according to the signals it senses. This suggests a note of caution regarding the adoption of therapies able to alter the composition of the HL-associated microenvironment, such as monoclonal-antibody-based humoral immunotherapies (e.g., Rituximab) or immunomodulatory drugs (e.g., lenalidomide) [138, 139]. On the other hand, other target therapies such as anti-CD30 antibodies and anti-NFkB drugs may provide a significant benefit in the limited but still significant fraction of chemoresistant HL patients.…”
Section: Extranodal Involvement By Hlmentioning
confidence: 99%
“…In contrast, a recent case series described tumor flare reactions in three patients receiving lenalidomide and methylprednisolone for treatment of refractory HL [47]. These reactions mimicked early tumor progression, but the authors reported that the signs and symptoms resolved upon treatment with anti-inflammatory agents and never recurred.…”
Section: Lenalidomidementioning
confidence: 92%
“…Lenalidomide has multiple modes of action, including direct induction of apoptosis in tumour cells, antiangiogenic effects, and the activation of immune cells, such as natural killer cells and T cells, enhancing Th1-type cellular immunity and natural killer T-cell cytotoxicity [253]. Preliminary results of some clinical trials of lenalidomide in HL have been recently reported [254–256]. In all studies, administration of oral daily lenalidomide in heavily pretreated HL patients induced clinical response ranging from 17 to 50%, and in most other patients disease stabilization was achieved.…”
Section: Therapeutic Strategies To Overcome Immune Escape In Hlmentioning
confidence: 99%